2019
DOI: 10.5194/amt-2019-265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An improved air mass factor calculation for NO<sub>2</sub> measurements from GOME-2

Abstract: Abstract. An improved tropospheric nitrogen dioxide (NO2) retrieval algorithm from the Global Ozone Monitoring Experiment-2 (GOME-2) instrument based on air mass factor (AMF) calculations performed with more realistic model parameters is presented. The viewing angle-dependency of surface albedo is taken into account by improving the GOME-2 Lambertian-equivalent reflectivity (LER) climatology with a directionally dependent LER (DLER) dataset over land and an ocean surface albedo parametrization over water. A pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(161 reference statements)
0
1
0
Order By: Relevance
“…2014;Kuhlman et al, 2015, Laughner et al, 2016Judd et al, 2019). Also Liu et al (2019c) showed that known uncertainties in albedo climatologies result in NO2 column uncertainties of 3-6%, while errors in model input are responsible for up to 20% of error on the retrieved NO2 columns. Looking at the details of the comparison results at each station ( Fig.…”
Section: Comparison Of Ground-based and Satellite Datasetsmentioning
confidence: 99%
“…2014;Kuhlman et al, 2015, Laughner et al, 2016Judd et al, 2019). Also Liu et al (2019c) showed that known uncertainties in albedo climatologies result in NO2 column uncertainties of 3-6%, while errors in model input are responsible for up to 20% of error on the retrieved NO2 columns. Looking at the details of the comparison results at each station ( Fig.…”
Section: Comparison Of Ground-based and Satellite Datasetsmentioning
confidence: 99%